Investigating Drivers for Success in Intrapreneurial Ventures within KPJ Group of Companies - Mohd Nor, Fariz Hamdi (2013)
One of the top ten list of dream for Generation Y is to own a business. Owning a business offers the flexibility, unlimited financial gain, gaining control, recognition from peer and opportunity for using creativity and innovation in a competitive market landscape. However, the question how to start a maximum potential and minimum risk business in the crowded marketplace? Johor Corporation (JCorp) in Malaysia has its own success story after came across the solution and founded a vehicle to achieve this dream. Kumpulan Perbadanan Johor (KPJ), a leader for Asian Private healthcare provider of JCorp has been creating a new breed of Intrapreneur of highly integrity, passion for result and innovation driven. With the development of controversial Waqf corporate concept and Business Jihad value, JCorp and KPJ has created blueprint of successful Intrapreneurship model. The study will be evaluating the unique characteristics of Intrapreneur in KPJ and the organisation climate that provide raison d’etre of the successful new venture creation.